Quick-setting and quick-sticking mold spraying concrete as well as preparation method and application thereof in tunnels

By developing fast-setting and fast-sticking sprayed concrete and using ingredients such as modified lithium salt and polyacrylamide, we have solved the problems of long construction time, high cost, excessive material waste, and poor concrete viscosity in tunnel construction, and achieved fast-setting, early-stage concrete. The effect of strong, impermeable and efficient construction.

CN119349967AActive Publication Date: 2025-01-24WUHAN UNIV OF TECH

Patent Information

Application Number
CN202411460958.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-24
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The existing technology has problems such as long construction time, high cost, high material waste, poor concrete viscosity, large rebound, low strength and durability in tunnel construction, which is difficult to meet the needs of fast support and efficient construction in tunnel construction.

Method used

Develop a fast-setting and fast-sticking shotcrete, which consists of fast-hardening sulphoaluminate cement, glass beads, modified lithium salt, modified attapulgite, polyacrylamide, carbon fiber, powdered petroleum wax, and machine-made sand , mechanical gravel and water, through the combination of modified lithium salt and polyacrylamide, the lithium salt molecules are fixed and released by heating before injection, the polyacrylamide improves the viscosity and impermeability, and carbon fiber and powdered petroleum wax are used to control Gently improves compactness.

Benefits of technology

Achieve the effect of fast condensation sticky, early strong anti -penetration, and efficient construction. The initial condensation time is shortened to 60-90s, the 8H compressive strength reaches 10 to 13MPa, the anti -seepage level reaches P8 level, the slump can reach 20-23cm It is suitable for construction in different tunnel environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005091853140000101
    Figure BDA0005091853140000101
Patent Text Reader

Abstract

The invention relates to quick-setting and quick-sticking mold spraying concrete as well as a preparation method and application thereof in a tunnel. The quick-setting and quick-sticking mold spraying concrete is prepared by mixing the following components in parts by weight: 380 to 420 parts of quick-hardening sulphoaluminate cement, 40 to 50 parts of glass beads, 10 to 20 parts of modified lithium salt, 40 to 50 parts of modified attapulgite, 10 to 20 parts of polyacrylamide, 40 to 50 parts of carbon fiber, 40 to 50 parts of powdery petroleum wax, 800 to 860 parts of machine-made sand, 860 to 900 parts of machine-made broken stone and 170 to 180 parts of water. During construction, the prepared mold spraying concrete is conveyed into a spraying machine with a mold plate, and slurry is properly heated and then sprayed to a tunnel working face through a spraying head to be rapidly cured. The mold spraying concrete has the advantages of being convenient to convey, efficient in construction, accurate in temperature control, stable in performance and the like, the initial setting time of the mold spraying concrete is shortened to 60-90 s, the 8-h compressive strength of the mold spraying concrete reaches 10-13 MPa, the bonding strength of the mold spraying concrete and surrounding rock can reach 1.5-3.0 MPa, the anti-permeability grade of the mold spraying concrete can reach the P8 grade, and the mold spraying concrete has good application prospects in various projects including tunnel construction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of inorganic non-metallic materials and tunnel construction, and in particular to a fast-setting and fast-adhesive formwork sprayed concrete and a preparation method thereof and application in tunnels. Background Art

[0002] Compared with ground construction, construction in tunnel environments mostly requires rapid support, and has higher requirements for the early strength and rapid solidification performance of concrete. The humid internal environment also puts forward higher requirements and standards for the durability, impermeability and other properties of concrete. In order to achieve high-efficiency construction of tunnels and good mechanical properties, impermeability and durability of tunnel concrete, it is necessary to choose a reasonable process, shorten the initial setting time of concrete as much as possible, increase the viscosity of concrete and the sprayed surface, and ensure the workability of concrete. In this context, the application of spray casting technology in tunnel construction has broad prospects.

[0003] The spraying technology mainly relies on shotcrete. Under the action of compressed air or other power sources, the concrete made of cementitious materials, aggregates, etc. in a certain proportion is sprayed at high speed onto the surface of rocks or buildings. Under the action of the quick-setting agent, it solidifies and hardens in a short time to produce a certain strength, forming a concrete structure with sealing and supporting functions. Traditional shotcrete has many problems in large-scale tunnel construction, such as long construction time, high construction cost, more material waste, poor concrete viscosity, large rebound, low strength and durability.

[0004] The search found that some scholars have disclosed an early-strength liquid accelerator and its preparation method (CN115636615A). This solution is to add a modified calcium silicate crystal solution to the alcoholized alkaline aluminum sol, and react for 3-4 hours to obtain an early-strength liquid accelerator. Other scholars have disclosed a liquid thickener for shotcrete and its preparation method and application (CN117886544A). This solution improves the bonding ability of latex powder through modification, thereby increasing the viscosity of the slurry. Analysis shows that although these existing solutions have overcome the problems of long initial setting time and poor workability to a certain extent, they will have an adverse effect on the workability and setting time of concrete, and the cost is generally high.

[0005] In this context, sprayed concrete technology has a better future in tunnel construction. Sprayed concrete technology combines the advantages of template fixation and wet sprayed concrete construction. It uses a sprayer with a template to spray concrete and then quickly solidifies it on the tunnel wall. As the sprayer moves, the working surface continues to expand. Sprayed concrete has stable quality, high construction efficiency, high strength and durability. The slump is generally 8 to 16 cm, the bonding strength with the surrounding rock is generally 0.5 to 2.0 MPa, the impermeability grade is generally P6, the initial setting time after adding the accelerator is generally 2 to 3 minutes, and it is generally a two-component spraying. The 8h compressive strength is 6 to 9 MPa, the 24h compressive strength is 9 to 15 MPa, and the 28d compressive strength is 30 to 33 MPa. When constructing in a tunnel environment, the concrete lining in the initial support stage needs to quickly reach a state close to the initial setting to provide sufficient support to prevent deformation of the surrounding rock. If the initial setting time is slightly longer, the concrete lining may crack and deform due to changes in temperature and humidity inside the tunnel, posing a serious threat to the tunnel construction and the lives of construction personnel.

[0006] Based on this, developing a type of sprayed concrete that has fast setting and adhesion, early strength and impermeability, and efficient construction, and ensuring that it has good stability and applicability in different tunnel environments is a technical challenge that needs to be solved urgently. Summary of the invention

[0007] One of the purposes of the present invention is to solve the above-mentioned problems existing in the prior art and to provide a fast-setting and fast-adhesive sprayed concrete, which comprises cement, glass beads, lithium salt, attapulgite, polyacrylamide, carbon fiber, powdered petroleum wax, machine-made sand, machine-made gravel and water.

[0008] Furthermore, the quick-setting and quick-adhesive sprayed concrete is composed of 380 to 420 parts of cement, 40 to 50 parts of glass beads, 10 to 20 parts of lithium salt, 40 to 50 parts of attapulgite, 10 to 20 parts of polyacrylamide, 40 to 50 parts of carbon fiber, 40 to 50 parts of powdered petroleum wax, 800 to 860 parts of machine-made sand, 860 to 900 parts of machine-made gravel, and 170 to 180 parts of water.

[0009] Furthermore, the cement is specifically fast-hardening sulphoaluminate cement, the lithium salt is specifically modified lithium salt, and the attapulgite is specifically modified attapulgite.

[0010] Furthermore, the preparation process of the modified lithium salt is specifically as follows: poly (N-isopropylacrylamide), lithium salt and water are uniformly mixed, and the water is removed after heating reaction to obtain the modified lithium salt.

[0011] Furthermore, the preparation process of the modified attapulgite is as follows: attapulgite and limestone are mixed evenly, then heated to 600-750° C., naturally cooled and sieved to obtain the modified attapulgite.

[0012] The second object of the present invention is to provide a method for preparing the above-mentioned fast-setting, fast-bonding formwork sprayed concrete, comprising: (a) mixing raw materials except water according to a formula to obtain dry material; (b) mixing the dry material with water to obtain fast-setting, fast-bonding formwork sprayed concrete slurry.

[0013] Furthermore, in step (a) and step (b), mixing is performed by stirring, the stirring speed does not exceed 60 r / min, and the stirring time does not exceed 10 min.

[0014] The third object of the present invention is to provide the application of the above-mentioned fast-setting and fast-adhesive sprayed concrete in tunnel construction.

[0015] Furthermore, the specific application method is as follows: the fast-setting and fast-adhesive sprayed concrete slurry is transported to a spray machine with a template, and the slurry is sprayed onto the tunnel working surface through a nozzle for rapid solidification.

[0016] Furthermore, the nozzle is flat, and two sides of the nozzle are arcs.

[0017] Furthermore, the fast-setting, fast-adhesive spray concrete slurry needs to be heated to 32°C-35°C before spraying.

[0018] Furthermore, the slurry heating is implemented as follows: a heating device is installed upstream of the nozzle, and the heating device is specifically an electric heater or a microwave heater.

[0019] Furthermore, the heating device is preferably an annular microwave heater, and the annular microwave heater is sleeved on the material conveying pipeline.

[0020] Furthermore, the spraying speed of the fast-setting and fast-adhesive sprayed concrete slurry is 10 to 15 m / s.

[0021] Compared with existing similar products or technologies, the advancement of the present invention is mainly reflected in the following points:

[0022] (1) Fast setting, fast adhesion, early strength and impermeability. The new type of mold sprayed concrete provided by the present invention is mixed with fast-hardening sulfoaluminate cement, glass microspheres, modified lithium salt, modified attapulgite, polyacrylamide, carbon fiber, powdered petroleum wax, machine-made sand, machine-made crushed stone and water. The lithium salt is modified to form an aggregate with poly N-isopropylacrylamide, thereby fixing the lithium salt molecules, avoiding the early contact of lithium salt with fast-hardening sulfoaluminate cement to affect the spraying construction. When the concrete slurry is heated to 32-35°C before spraying, the lithium salt gradually dissolves. The released lithium salt can accelerate the hydration process, shorten the initial setting time to 60-90s and improve the early strength. The 8h compressive strength can reach 10-13MPa. The polyacrylamide molecular chain in the raw material carries a negative charge, which can absorb the positive charge in the concrete system, thereby improving the viscosity of the concrete and improving the impermeability. The test results show that the bonding strength of the mold sprayed concrete with the surrounding rock can reach 1.5-3.0MPa, and the impermeability grade can reach P8.

[0023] (2) Convenient transportation and efficient construction. The present invention enhances the plasticity of concrete with modified attapulgite and also utilizes the "ball" effect of glass microspheres. Modified attapulgite is prepared by calcining attapulgite and limestone together and then screening. The calcined attapulgite has an inorganic thickening effect, so it can improve the plasticity of concrete. Calcinated limestone generates calcium hydroxide after contact with water. The layered calcium hydroxide crystals can play a lubricating role. At the same time, the reaction releases a lot of heat and can accelerate hydration and condensation. The surface of glass microspheres is smooth, which can reduce the friction resistance of the concrete system, making it easier to flow, which is conducive to the transportation of mold sprayed concrete in the spraying equipment. In addition, glass microspheres can also fill the gaps inside the concrete to improve the compactness and strength of the concrete. Through the matching use of modified attapulgite and glass microspheres, the adverse effects on the workability of concrete caused by the extremely short initial setting time are solved, ensuring that the concrete has excellent plasticity and smooth spraying, and the slump can reach 20 to 23 cm.

[0024] (3) Precise temperature control and stable use. The present invention uses carbon fiber and powdered petroleum wax as the absorbing material and temperature control material respectively. The heating rate of carbon fiber during microwave heating is about 1.0-1.2°C / s, which can quickly increase the temperature of concrete by 10-40°C. Powdered petroleum wax can absorb latent heat and undergo phase change when the concrete temperature is higher than 40°C, thereby preventing the concrete temperature from being too high. The coordinated use of carbon fiber and powdered petroleum wax solves the problem of the initial setting of concrete hydration caused by the damp and cold environment of the tunnel, and can precisely control the temperature of the concrete, so that the mold sprayed concrete has good stability and applicability in different tunnel environments.

[0025] (4) Single-component spraying. The present invention improves and innovates the spray head for molded concrete. The nozzle is flat and can produce a wider spray surface, realizing large-area, fast and efficient spraying. In addition, an annular microwave heater is installed upstream of the special nozzle, with a length of 20 to 30 cm, a distance of 20 to 40 cm from the nozzle, a microwave power of 80 to 100 kW, and a microwave frequency of 2.45 GHz. The annular microwave heater is used to heat the concrete slurry transported to the nozzle to ensure that the lithium salt is gradually dissolved from the aggregate and is homogeneously mixed with the fast-hardening sulfoaluminate cement to react rapidly. This design adapts to the short initial setting time of molded concrete. The spraying can be completed using a single nozzle, which changes the conventional operation of two-component spraying. DETAILED DESCRIPTION

[0026] In order to enable those skilled in the art to fully understand the technical solutions and beneficial effects of the present invention, further description is given below in conjunction with specific embodiments.

[0027] The fast-setting and quick-adhesive sprayed concrete for tunnels provided by the present invention has a formula of 380-420 parts by weight of fast-hardening sulphoaluminate cement, 40-50 parts by weight of glass microspheres, 10-20 parts by weight of modified lithium salt, 40-50 parts by weight of modified attapulgite, 10-20 parts by weight of polyacrylamide, 40-50 parts by weight of carbon fiber, 40-50 parts by weight of powdered petroleum wax, 800-860 parts by weight of machine-made sand, 860-900 parts by weight of machine-made crushed stone, and 170-180 parts by weight of water.

[0028] The preparation method of the modified lithium salt is as follows: poly N-isopropylacrylamide and lithium salt are mixed with deionized water to prepare a solution with a concentration of 0.5%-1%, and the poly N-isopropylacrylamide aqueous solution and the lithium salt aqueous solution are mixed uniformly at a mass ratio of 1:1 to 3:1 at 15-20°C, and the resulting mixture is heated to 32-35°C at a heating rate of 2-5°C / min in an air atmosphere and kept warm for 0.5-2h. During this period, poly N-isopropylacrylamide undergoes a phase change and forms aggregates with the lithium salt, thereby fixing the lithium salt molecules. Subsequently, the mixture is cooled to 15-26°C, and solid-liquid separation is performed by vacuum filtration or filter pressing, and the separated solid is washed 2-3 times with a small amount of deionized water. The washed modified lithium salt solid is evenly spread on a drying tray with a thickness not exceeding 6mm, and then placed in a constant temperature oven at 15-26°C for blast drying for 24-48h, thereby obtaining a modified lithium salt. The raw material lithium salt can be one or more of lithium carbonate, lithium sulfate, lithium chloride, lithium nitrate, lithium hydroxide, etc., and the purity of the prepared modified lithium salt is above 99%.

[0029] The preparation method of modified attapulgite is as follows: attapulgite and limestone are uniformly mixed in a mass ratio of 2:1 to 4:1, the resulting mixture is heated to 600 to 750°C at a heating rate of 5 to 20°C / min in an air atmosphere and kept warm for 10 to 30 minutes, then naturally cooled to room temperature, and sieved with a 100 to 200 mesh sieve to obtain modified attapulgite.

[0030] After weighing the raw materials according to the above ratio, add glass beads, carbon fiber, polyacrylamide, modified lithium salt, powdered petroleum wax, machine-made sand, machine-made gravel, fast-hardening sulphoaluminate cement and modified attapulgite into the mixing pot in turn, start the stirring device and dry mix at a speed of 30-60r / min for 2-5min, then add water and stir at the same speed for 1-3min to obtain fast-setting and fast-adhesive spray concrete slurry.

[0031] After the fast-setting and fast-adhering spray concrete slurry is prepared, it is transported to a spray machine with a template through a pipeline, and the slurry is sprayed out from the nozzle at a speed of 10 to 15 m / s to quickly solidify. In order to fully dissolve the lithium salt and react with the fast-hardening sulphoaluminate cement, a ring-shaped microwave heater with a length of 20 to 30 cm is installed at a distance of 20 to 40 cm from the nozzle in the direction of the incoming material, and the microwave frequency band is 2.45 GHz, so that the slurry temperature can be controlled at 32°C-35°C. In order to obtain a wider spraying surface and realize large-area rapid and efficient spraying, the nozzle is designed to be flat, and the two sides of the nozzle are arcs with a radius of 2 to 3 cm, the maximum width of the nozzle is 10 to 12 cm, and the height is 4 to 6 cm.

[0032] Example 1

[0033] The formula of the fast-setting, fast-bonding sprayed concrete for tunnels provided in this embodiment is: 390 parts of fast-hardening sulphoaluminate cement, 44 parts of glass microspheres, 16 parts of modified lithium salt, 44 parts of modified attapulgite, 16 parts of polyacrylamide, 44 parts of carbon fiber, 46 parts of powdered petroleum wax, 820 parts of machine-made sand, 880 parts of machine-made crushed stone, and 172 parts of water. The preparation method of the fast-setting, fast-bonding sprayed concrete for tunnels is as follows:

[0034] S1. Add glass microbeads, carbon fiber, polyacrylamide, modified lithium salt, powdered petroleum wax, machine-made sand, machine-made gravel, fast-hardening sulphoaluminate cement, and modified attapulgite into a stirring pot in proportion, and dry-mix at a speed of 30 r / min for 2 min to obtain a uniformly mixed dry material;

[0035] S2, adding water to the dry material in step S1, stirring at a speed of 30r / min for 1min to obtain a slurry;

[0036] S3. The slurry in step S2 is heated to 32° C.-35° C. and then sprayed out from the nozzle at a speed of 10 m / s. The slurry is quickly solidified on the tunnel working surface.

[0037] Example 2

[0038] The formula of the fast-setting and fast-bonding sprayed concrete for tunnels provided in this embodiment is: 404 parts of fast-hardening sulphoaluminate cement, 42 parts of glass beads, 14 parts of modified lithium salt, 44 parts of modified attapulgite, 16 parts of polyacrylamide, 44 parts of carbon fiber, 46 parts of powdered petroleum wax, 830 parts of machine-made sand, 870 parts of machine-made gravel, and 175 parts of water.

[0039] S1. Add glass microbeads, carbon fiber, polyacrylamide, modified lithium salt, powdered petroleum wax, machine-made sand, machine-made gravel, fast-hardening sulphoaluminate cement, and modified attapulgite into a stirring pot in proportion, and dry-mix at a speed of 60 r / min for 3 min to obtain a uniformly mixed dry material;

[0040] S2, adding water to the dry material in step S1, stirring at a speed of 60r / min for 3min to obtain a slurry;

[0041] S3, heating the slurry in step S2 to 32°C-35°C and then spraying it out from the nozzle at a speed of 15m / s, and the slurry quickly solidifies on the tunnel working surface.

[0042] Example 3

[0043] The formula of the fast-setting and fast-bonding sprayed concrete for tunnels provided in this embodiment is: 410 parts of fast-hardening sulphoaluminate cement, 46 parts of glass beads, 17 parts of modified lithium salt, 46 parts of modified attapulgite, 13 parts of polyacrylamide, 46 parts of carbon fiber, 43 parts of powdered petroleum wax, 845 parts of machine-made sand, 880 parts of machine-made gravel, and 176 parts of water.

[0044] S1. Add glass microbeads, carbon fiber, polyacrylamide, modified lithium salt, powdered petroleum wax, machine-made sand, machine-made gravel, fast-hardening sulphoaluminate cement, and modified attapulgite into a stirring pot in proportion, and dry-mix at a speed of 50 r / min for 4 min to obtain a uniformly mixed dry material;

[0045] S2, adding water to the dry material in step S1, stirring at a speed of 40r / min for 2min to obtain a slurry;

[0046] S3. The slurry in step S2 is heated to 32° C.-35° C. and then sprayed out from the nozzle at a speed of 12 m / s. The slurry is quickly solidified on the tunnel working surface.

[0047] Example 4

[0048] The formula of the fast-setting and fast-bonding sprayed concrete for tunnels provided in this embodiment is: 386 parts of fast-hardening sulphoaluminate cement, 42 parts of glass beads, 15 parts of modified lithium salt, 45 parts of modified attapulgite, 15 parts of polyacrylamide, 45 parts of carbon fiber, 47 parts of powdered petroleum wax, 837 parts of machine-made sand, 886 parts of machine-made gravel, and 174 parts of water.

[0049] S1. Add glass microbeads, carbon fiber, polyacrylamide, modified lithium salt, powdered petroleum wax, machine-made sand, machine-made gravel, fast-hardening sulphoaluminate cement, and modified attapulgite into a stirring pot in proportion, and dry-mix at a speed of 50 r / min for 4 min to obtain a uniformly mixed dry material;

[0050] S2, adding water to the dry material in step S1, stirring at a speed of 30r / min for 2min to obtain a slurry;

[0051] S3. The slurry in step S2 is heated to 32° C.-35° C. and then sprayed out from the nozzle at a speed of 14 m / s. The slurry is quickly solidified on the tunnel working surface.

[0052] Example 5

[0053] The formula of the fast-setting and fast-bonding sprayed concrete for tunnels provided in this embodiment is: 415 parts of fast-hardening sulphoaluminate cement, 44 parts of glass beads, 14 parts of modified lithium salt, 48 parts of modified attapulgite, 17 parts of polyacrylamide, 42 parts of carbon fiber, 47 parts of powdered petroleum wax, 825 parts of machine-made sand, 867 parts of machine-made gravel, and 177 parts of water.

[0054] S1. Add glass microbeads, carbon fiber, polyacrylamide, modified lithium salt, powdered petroleum wax, machine-made sand, machine-made gravel, fast-hardening sulphoaluminate cement, and modified attapulgite into a stirring pot in proportion, and dry-mix at a speed of 40 r / min for 3 min to obtain a uniformly mixed dry material;

[0055] S2, adding water to the dry material in step S1, stirring at a speed of 50r / min for 3min to obtain a slurry;

[0056] S3. The slurry in step S2 is heated to 32° C.-35° C. and then sprayed out from the nozzle at a speed of 13 m / s. The slurry is quickly solidified on the tunnel working surface.

[0057] Example 6

[0058] The formula of the fast-setting and fast-bonding sprayed concrete for tunnels provided in this embodiment is: 400 parts of fast-hardening sulphoaluminate cement, 48 parts of glass beads, 12 parts of modified lithium salt, 48 parts of modified attapulgite, 18 parts of polyacrylamide, 42 parts of carbon fiber, 42 parts of powdered petroleum wax, 855 parts of machine-made sand, 870 parts of machine-made gravel, and 179 parts of water.

[0059] S1. Add glass microbeads, carbon fiber, polyacrylamide, modified lithium salt, powdered petroleum wax, machine-made sand, machine-made gravel, fast-hardening sulphoaluminate cement, and modified attapulgite into a stirring pot in proportion, and dry-mix at a speed of 40 r / min for 5 min to obtain a uniformly mixed dry material;

[0060] S2, adding water to the dry material in step S1, stirring at a speed of 30r / min for 3min to obtain a slurry;

[0061] S3. The slurry in step S2 is heated to 32° C.-35° C. and then sprayed out from the nozzle at a speed of 11 m / s. The slurry is quickly solidified on the tunnel working surface.

[0062] Comparative Example 1

[0063] The difference between this comparative example and Example 1 is that this comparative example does not use modified lithium salt. In order to ensure that the proportions of other components remain unchanged, 16 parts of modified lithium salt are replaced by 16 parts of machine-made sand.

[0064] The formula of the fast-setting and quick-bonding sprayed concrete for tunnels provided in this comparative example is: 390 parts of fast-hardening sulphoaluminate cement, 44 parts of glass beads, 44 parts of modified attapulgite, 16 parts of polyacrylamide, 44 parts of carbon fiber, 46 parts of powdered petroleum wax, 836 parts of machine-made sand, 880 parts of machine-made crushed stone, and 172 parts of water.

[0065] Comparative Example 2

[0066] The difference between this comparative example and Example 2 is that this comparative example does not use modified attapulgite. In order to ensure that the proportions of other components remain unchanged, 44 parts of modified attapulgite are replaced by 44 parts of machine-made sand.

[0067] The formula of the fast-setting and fast-bonding sprayed concrete for tunnels provided in this embodiment is: 404 parts of fast-hardening sulphoaluminate cement, 42 parts of glass beads, 14 parts of modified lithium salt, 16 parts of polyacrylamide, 44 parts of carbon fiber, 46 parts of powdered petroleum wax, 874 parts of machine-made sand, 870 parts of machine-made gravel, and 175 parts of water.

[0068] Comparative Example 3

[0069] The difference between this comparative example and Example 3 is that polyacrylamide is not used in this comparative example. In order to ensure that the proportions of other components remain unchanged, 13 parts of polyacrylamide are replaced by 13 parts of machine-made sand.

[0070] The formula of the fast-setting and fast-bonding sprayed concrete for tunnels provided in this embodiment is: 410 parts of fast-hardening sulphoaluminate cement, 46 parts of glass beads, 17 parts of modified lithium salt, 46 parts of modified attapulgite, 46 parts of carbon fiber, 43 parts of powdered petroleum wax, 858 parts of machine-made sand, 880 parts of machine-made gravel, and 176 parts of water.

[0071] The initial setting time, bonding strength with surrounding rock, slump, 8h compressive strength and impermeability grade of the fast-setting and fast-bonding sprayed concrete for tunnels prepared in Examples 1-6 and Comparative Examples 1-3 were tested. Among them, the setting time test was carried out with reference to GB / T 1346-2011 "Test Method for Water Consumption, Setting Time and Stability of Cement Standard Consistency", the bonding strength test was carried out with reference to JGJ / T 372-2016 "Technical Specification for Application of Sprayed Concrete", the slump test was carried out with reference to GB / T 50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures", the 8h compressive strength test was carried out with reference to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the specimen size was 150mm×150mm×150mm, and the impermeability grade test was carried out with reference to GB50164-2011 "Concrete Quality Control Standard", and the specific test results are shown in the following table.

[0072] Table 1 Performance comparison table of sprayed concrete prepared in different embodiments

[0073]

[0074] As can be seen from the above table, ① the initial setting time and 8h compressive strength of the fast-setting, fast-bonding mold sprayed concrete for tunnels using modified lithium salts (Examples 1-6, Comparative Examples 2 and Comparative Examples 3) are significantly better than those of the fast-setting, fast-bonding mold sprayed concrete for tunnels not using modified lithium salts (Comparative Example 1), that is, the modified lithium salt can accelerate the hydration process, shorten the initial setting time to 60-90s, and improve the early strength. ② The slump of the fast-setting, fast-bonding mold sprayed concrete for tunnels using modified attapulgite (Examples 1-6, Comparative Examples 1 and Comparative Examples 3) is significantly greater than that of the fast-setting, fast-bonding mold sprayed concrete for tunnels not using modified attapulgite (Comparative Example 2), which shows that the modified attapulgite has an inorganic thickening effect and can improve the plasticity of concrete. ③ The bonding strength and impermeability grade of the fast-setting, quick-bonding sprayed concrete for tunnels using polyacrylamide (Examples 1-6, Comparative Examples 1 and 2) with the surrounding rock are significantly better than those of the fast-setting, quick-bonding sprayed concrete for tunnels not using polyacrylamide (Comparative Example 3). This is because the molecular chain of polyacrylamide carries a negative charge, which can absorb the positive charge in the concrete system, improve the viscosity of the concrete, and improve the impermeability.

[0075] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit and essential features of the present invention. Therefore, the embodiments should be regarded as exemplary and non-restrictive from all points of view, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent terms of the claims are included in the present invention.

Claims

1. A fast-setting, fast-adhesive sprayed concrete, characterized in that: The fast-setting and quick-adhesive sprayed concrete comprises cement, glass microspheres, lithium salt, attapulgite, polyacrylamide, carbon fiber, powdered petroleum wax, machine-made sand, machine-made crushed stone and water.

2. The fast-setting, fast-adhering formwork sprayed concrete according to claim 1, characterized in that: The quick-setting and quick-adhesive sprayed concrete is composed of 380-420 parts of cement, 40-50 parts of glass microspheres, 10-20 parts of lithium salt, 40-50 parts of attapulgite, 10-20 parts of polyacrylamide, 40-50 parts of carbon fiber, 40-50 parts of powdered petroleum wax, 800-860 parts of machine-made sand, 860-900 parts of machine-made crushed stone and 170-180 parts of water.

3. The fast-setting, fast-adhering formwork sprayed concrete according to claim 1 or 2, characterized in that: The cement is specifically fast-hardening sulphoaluminate cement, the lithium salt is specifically modified lithium salt, and the attapulgite is specifically modified attapulgite.

4. The method for preparing the fast-setting, fast-adhesive sprayed concrete according to any one of claims 1 to 3, characterized in that The method comprises: mixing raw materials except water evenly to obtain dry materials, and mixing the dry materials and water evenly to obtain fast-setting and fast-adhesive formwork sprayed concrete slurry.

5. Application of the fast-setting, fast-adhesive sprayed concrete described in any one of claims 1 to 3 in tunnel construction.

6. The use according to claim 5, characterized in that The specific process of this application is: the fast-setting and quick-adhesive sprayed concrete slurry is transported to a spray machine with a template, and the slurry is sprayed onto the tunnel working surface through a nozzle for rapid solidification.

7. The use according to claim 6, characterized in that: The nozzle is flat, and two sides of the nozzle are arcs.

8. The use according to claim 6, characterized in that: Quick-setting, quick-adhesive spray concrete slurry also needs to be heated to 32℃-35℃ before spraying.

9. The use according to claim 8, characterized in that The slurry heating is implemented in the following way: a heating device is installed upstream of the nozzle, the heating device is specifically an electric heater or a microwave heater, and the heating device is mounted on the material delivery pipeline.

10. The use according to claim 6, characterized in that: The spraying speed of fast-setting and fast-adhesive sprayed concrete slurry is 10 to 15 m / s.

Citation Information

Patent Citations

  • Alkali-free chlorine-free fluorine-free early-strength liquid accelerator and preparation method thereof

    CN115636615A

  • Liquid tackifier for sprayed concrete as well as preparation method and application of liquid tackifier

    CN117886544A

  • Early-strength sprayed concrete

    CN105503102A

  • C30 high performance concrete and preparation method thereof

    CN106995301A

  • Precast dry-mix sprayed concrete

    CN108793935A

Cited By

  • Underground tunnel excavation and support method

    CN120626176A

  • Underground tunnel excavation and support method

    CN120626176B